La Lateralidad y su relación con el desarrollo Psicomotor grueso en los niños y niñas de 3 años en las instituciones educativas del Nivel Inicial N° 288 y 231 del sector Atahualpa de la ciudad de Rioja, en el año 2013 - Vargas Dávila, Luis Charles (2014)
This research aims to determine the correlation between laterality with thick psychomotor development in children 3 years in educational institutions of the initial level N ° 288 and 231 of Atahualpa sector of the city of Rioja in 2013. The study is important because it reveals the presence of laterality, and how this is related to gross motor skills. The central aim of the research was to determine the relationship between laterality with thick psychomotor development in children 3 years in educational institutions of the Initial level N ° 288 and 231 of Atahualpa Sector city Rioja; and specific objectives were to identify laterality in children 3 years in educational institutions of the Initial level N ° 288 and 231 describe the bulk psychomotor development in children 3 years in educational institutions of the Initial level N ° 288 and 231, and to establish the relationship between laterality thick with psychomotor development in children 3 years in educational institutions of the Initial level N ° 288 and 231. Laterality is based on the theoretical assumptions of S. Estevez and others (2009), R. Paricio and others (2003) and Roig (1968), which explains the functional domain on one side of the body when performing motor actions; and psychomotor development in thick Rigal (2001), Berruezo (2000), Pine (2011), Tehran (2011), and dark-haired Camisán (2013) and Bravo and Hurtado (2012), exhibiting thick psychomotor development through of the skills and abilities to perfect their moves. They give us sufficient theoretical tools to pose the following hypothesis: There is significant relationship between laterality thick with psychomotor development in children 3 years in educational institutions of the Initial level N ° 288 and 231. Methodologically, the research design was descriptive-correlational study, with a sample of 25 children from 288 educational institutions and 231 and in the process of statistical analysis it was found that the central or research hypothesis is accepted with a 95% confidence, the same as is evident in the graph of Gaussian curve and the value obtained from the Pearson correlation coefficient s 0,9676 being a very strong positive correlation and that is explained by the 93.63% of the population